Pregnant women’s social representations of oral health: a reference to rethink mother-baby dental assistance - Finkler, Mirelle (Online Brazilian Journal of Nursing, 2005)
Assuming that a better understanding is crucial to a better practice, we searched for pregnant women’s knowledge about oral health, seeking to understand the social representations (SR) that influence their practice, from the perspective of the Social Representation Theory purposed by Moscovici (1961). The subjects of this qualitative research were 12 pregnant women enrolled in prenatal care services. Each woman was assessed by means of a semistructured interview, which was recordered and transcripted. Pre-categories came out from the data analysis and were gathered in 14 thematic clusters: profile, seeking for dental care, learned issues, self-care, concepts and values on oral health, pregnancy versus dental care, need for professional information, relationship between mother and child ́s oral health, responsibility, wishes, child care and other issues. Four major themes were extracted from latter grouping of these clusters: pregnant woman profile, SR of pregnant woman’s oral health, SR of relationship between oral health and pregnancy and SR of child’s oral health. In our data analyzes and discussion we intended highlight topics that could contribute to enhance the health workers’ skills by providing reflections about the ongoing model for pregnant women dental care. To do so, we outlined issues as the representation of dental care during childbearing as harmful to the child, the representation of the influence of mother’s oral health on child’s health, mediated by the sense of unity between pregnant women and their babies, and the persistence of this intimacy after labor, by the shared health care issues and by the examples extended from the mothers to their children. The beginning of a promising cycle of a better oral health promotion depends on a closer approach of dentistry to pregnant women. Therefore it is necessary to rethink the human resources training (specially in dentistry) and the dental practice in health care systems, emphasizing inquisitive education, interdisciplinary prenatal assistance and comprehensive dental assistance to the pregnant woman. We also outlined suggestions attempting to provide issues for research and to contribute for the improvement of mother-baby dental care.